Factors affecting how the youth in the townships use internet to seek employment: case of a township in Cape Town - Kunene, Khaya (Department of Information Systems, 2020)
Problem Statement: South Africa is currently facing a challenge of youth unemployment. The hardest hit are those from low income communities, as they in addition have limited access to information. The Internet has proven to be one of the ways in which recruitment is done and failure to access reduces the opportunities. The purpose of the research: The main objective of this study was to understand how the youth living in the townships use the Internet to seek for employment. The purpose of this study is to assess how the Internet use affect the youth when searching for employment. Design/methodology/ approach: An interpretivist approach was employed to understand how the youth seek employment. This study used a qualitative approach to collect the data. Interviews were done using semi-structured questions. Alampay (2006) Capability Approach (CA) was used as a guide to conceptualise how the youth from low-income communities use the Internet to find employment. Borrowing from the four main constructs (conversion factors, freedom, capabilities and functionings) employed by Alampay (2006) in his model, this study operationalised the Alampay (2006) CA model by adding the ICT commodities as the fifth construct. The CA was chosen as an appropriate framework for this study because the framework focuses on what humans are able to do and achieve when presented with the available ICT resources. Findings: The findings demonstrate that the lack of resources, income, information and digital skills affected the individual capabilities to effectively use the Internet when seeking employment. The success rate in finding a job using the Internet was low among job seekers. Commodities, individual differences, social and environmental factors affected how the youth (18-34 years) from low-income communities use the Internet to find employment. In addition, crime, poor network coverage, expensive data bundles and limited access to ICT resources were among the key factors that contributed to limited use of the Internet among job seekers. Research Contribution: This study seeks to close the gap in limited knowledge available in developing countries with regards to the use of the Internet among job seekers. Therefore, based on the study findings, this thesis has contributed towards adding value to the body of knowledge within the field of Information Systems. In addition, the findings can contribute towards assisting policy makers in solving challenges faced by the unemployment youth in developing countries when using technology to find employment.